Cognitive reserve attenuates the association between HIV serostatus and cognitive performance in adults living in the Deep South - Pope, Caitlin N. (Appl Neuropsychol Adult, 2022)
Cognitive reserve has shown evidence of mitigating HIV-related effects on cognition in people living with HIV (PWH). In a sample of adults residing in the Deep South, an underrepresented subgroup in the neuroAIDS literature, we assessed the association between HIV serostatus and age on processing speed, visual attention, executive function, and episodic memory and the attenuating effect of cognitive reserve. Adults (n = 138; 72 PWH; Mage = 58.7 years, SD = 7.9 years; 75% non-White race) were recruited from a university clinic and the community. Verbal abilities served as a proxy for cognitive reserve. Regressions accounting for race, alcohol usage, and depressive symptoms were conducted for each cognitive outcome. Indirect effects were tested using the PROCESS macro. Being HIV seropositive was associated with worse executive function (b = -1.04, SE = 0.38, p = .007) and episodic memory (b = -39.94, SE = 12.54, p = .002) performance. Every year of age above the mean and non-White race was associated with worse cognitive performance (ps < .05). The addition of cognitive reserve to the model attenuated the HIV serostatus associations with executive function (BC 95% CI -0.770, -0.001) along with most associations between race and cognitive outcomes. Age associations remained for all cognitive outcomes (ps < .05). Findings highlight the importance of including verbal ability proxies of cognitive reserve when assessing cognition in PWH. Highlighting modifiable cognitive processes, such as cognitive reserve, will further the development of targeted cognitive interventions in this at-risk population.